Modafinil as a Catecholaminergic Agent: Empirical Evidence and Unanswered Questions - Wisor, Jonathan P. (Frontiers in Neurology, 2013)
Modafinil, in its two clinical formulations (Provigil® and Nuvigil®), is a widely prescribed wake-promoting therapeutic agent. It binds competitively to the cell membrane dopamine transporter and is dependent on catecholaminergic (dopaminergic and adrenergic) signaling for its wake-promoting effects. The clinical spectrum of effects for modafinil is distinct from the effects seen with other catecholaminergic agents. Relative to other commonly used agents that act through catecholaminergic mechanisms, modafinil has a relatively low abuse potential, produces wakefulness with an attenuated compensatory sleep recovery thereafter, and does not ameliorate cataplexy in narcolepsy. These clinically relevant phenomenological differences between modafinil and agents such as amphetamines and cocaine do not eliminate catecholaminergic effects as a possible mediator of its wake-promoting action; they merely reflect its unique pharmacological profile. Modafinil is an exceptionally weak, but apparently very selective, dopamine transporter inhibitor. The pharmacodynamic response to modafinil, as measured by dopamine levels in brain microdialysate, is protracted relative to other agents that act via catecholaminergic mechanisms. The conformational constraints on the interaction of modafinil with the dopamine transporter—and probably, as a consequence, its effects on trace amine receptor signaling in the catecholaminergic cell—are unique among catecholaminergic agents. These unique pharmacological properties of modafinil should be considered both in seeking to thoroughly understand its putatively elusive mechanism of action and in the design of novel therapeutic agents.